2013
DOI: 10.1172/jci64410
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor ATF3 links host adaptive response to breast cancer metastasis

Abstract: Host response to cancer signals has emerged as a key factor in cancer development; however, the underlying molecular mechanism is not well understood. In this report, we demonstrate that activating transcription factor 3 (ATF3), a hub of the cellular adaptive response network, plays an important role in host cells to enhance breast cancer metastasis. Immunohistochemical analysis of patient tumor samples revealed that expression of ATF3 in stromal mononuclear cells, but not cancer epithelial cells, is correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(127 citation statements)
references
References 55 publications
(73 reference statements)
6
121
0
Order By: Relevance
“…On the contrary, if ATF3 expression in breast cancer cells was silenced by the siATF3 transfection or was suppressed by the signalling pathway inhibitor LY204002, breast cancer radioresistance could be relieved to a great extent and the radiation therapy efficiency can be also improved. Overwhelming evidence showed that ATF3 was highly expressed and was closely related to cell migration in breast cancer 6, 18. Gokulnath et al found that silencing of ATF3 expression could also decrease the production of MMP‐13 and Runx2 genes related to invasive and metastatic 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, if ATF3 expression in breast cancer cells was silenced by the siATF3 transfection or was suppressed by the signalling pathway inhibitor LY204002, breast cancer radioresistance could be relieved to a great extent and the radiation therapy efficiency can be also improved. Overwhelming evidence showed that ATF3 was highly expressed and was closely related to cell migration in breast cancer 6, 18. Gokulnath et al found that silencing of ATF3 expression could also decrease the production of MMP‐13 and Runx2 genes related to invasive and metastatic 18.…”
Section: Discussionmentioning
confidence: 99%
“…Overpowering evidence proved that ATF3 translated by an immediate early gene and its expression is weak in various cells. But ATF3 expression can be triggered by multiple cellular signals 6. According to existing investigations, ATF3 is supposed to be a crossroad of the cellular response network and ATF3 have been proved to take a place on canceration course of breast epithelial cells 7.…”
Section: Introductionmentioning
confidence: 99%
“…Stress also can indirectly promote cancer by weakening the immune system through releasing high levels of cortisol and epinephrine. Many studies have shown that these hormones make breast, ovarian and prostate cancer cells resistant to destruction [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…TAMs also promote breast cancer cell survival through α4-integrin-dependent binding of macrophage to vascular cell adhesion molecule-1 (VCAM-1)-expressing tumor cells, which favors breast cancer cell metastatic colonization . Wolford et al (2013) showed that induction of the expression of ATF3 and its downstream gene matrix metalloproteinase-9 (MMP-9) in macrophages leads to enhanced breast cancer invasiveness and metastasis. Ishihara et al (2013) revealed that Wiskott-Aldrich syndrome protein (WASp)-mediated EGF shedding by TAMs was required to enhance breast cancer motility, intravasation, and metastasis.…”
Section: Macrophagesmentioning
confidence: 99%